1977
DOI: 10.1148/122.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Demonstration of Intrahepatic Arterio-Portal Anastomoses in Hepatocellular Carcinoma

Abstract: Hepatic angiograms of 114 patients with hepatocellular carcinoma (HCC) were studied, particularly changes in the portal vein branches. Arterio-portal shunts of varying sizes, evidenced by opacification of intrahepatic portal branches, were seen in 72 cases (63.2%), with retrograde opacification of the portal vein trunk in 29 (25.4%). At least four types of shunts were found: (a) through a tumor thrombus in the portal branch, (b) in a retrograde direction via a peripheral tumor nodule, (c) through a small tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
51
1
3

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(55 citation statements)
references
References 4 publications
0
51
1
3
Order By: Relevance
“…Despite their application to the surgical resection of liver malignancies, however, recurrences are frequently found in the early postoperative period. It as yet remains unclear whether such lesions are due to pre-existing microscopic disease, result from surgical manipulation, or both.According to Okuda et al (1977), intrahepatic arterioportal anastomosis is demonstrated in 63.2% of patients with hepatocellular carcinoma, and retrograde flow of the portal vein trunk is seen in 25.4% as revealed by angiography. Therefore, tumour cell release into the portal vein during surgical treatment for liver malignancies may increase the metastasis of tumour to the liver.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their application to the surgical resection of liver malignancies, however, recurrences are frequently found in the early postoperative period. It as yet remains unclear whether such lesions are due to pre-existing microscopic disease, result from surgical manipulation, or both.According to Okuda et al (1977), intrahepatic arterioportal anastomosis is demonstrated in 63.2% of patients with hepatocellular carcinoma, and retrograde flow of the portal vein trunk is seen in 25.4% as revealed by angiography. Therefore, tumour cell release into the portal vein during surgical treatment for liver malignancies may increase the metastasis of tumour to the liver.…”
mentioning
confidence: 99%
“…According to Okuda et al (1977), intrahepatic arterioportal anastomosis is demonstrated in 63.2% of patients with hepatocellular carcinoma, and retrograde flow of the portal vein trunk is seen in 25.4% as revealed by angiography. Therefore, tumour cell release into the portal vein during surgical treatment for liver malignancies may increase the metastasis of tumour to the liver.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Conversely, several studies on the diagnosis of FNH have shown the importance of the drainage vessels. [10][11][12] Fukukura et al 10 studied the drainage vessels of FNH by injecting gelatin into the hepatic artery and portal vein of liver from autopsy and reported 2 pathways of vascular drainage in FNH. In the first pathway, blood entering the nodule from anomalous arteries drains directly into the hepatic veins.…”
Section: Discussionmentioning
confidence: 99%
“…An autopsy study reported that direct draining from the FNH into hepatic veins was seen in 31% of the FNH cases, whereas a direct hepatic vein drainage pattern was seen in only 1.8% of HCC cases. 11 Although drainage into hepatic veins has also been studied in detail with single-level dynamic CT during hepatic arteriography, the connection between the hepatic arteries and hepatic veins is not clear. In our present case, Levovistenhanced sonography was able to depict realtime drainage from the center of the tumor directly into the hepatic veins.…”
Section: Discussionmentioning
confidence: 99%